Patient and public involvement in academic clinical research in Switzerland – a mixed methods study - Deborah Eberle; Annina Baur; Cordula Landgraf; Joëlle Roos; Regina Grossmann (Swiss Medical Weekly)
BACKGROUND: While patient and public involvement (PPI) in clinical research contributes substantially to research ethics, feasibility and quality, the uptake and implementation of PPI-based approaches in Switzerland remain unknown. This study aimed to evaluate the current state and acceptance of PPI in academic clinical research in Switzerland, with the goal of developing recommendations for its future implementation and development.